AN EXAMINATION OF THE OF IMPACT OF MONETARY POLICY ON NIGERIAN ECONOMY - Emmanuel Ola, Adeyi; Kangrot Dorcas, Miapwap (GOMBE JOURNAL OF ADMINISTRATION AND MANAGEMENT (GJAM), 2019)
Macroeconomic management in an open economy to stimulate economic stability and growth for economic development through monetary policy and its impact on economy is one of the major concern of every economy. This paper examined the impact of monetary policy on Nigerian economy. The paper utilized the Ordinary Least Square (OLS) technique through multiple regression on the data sourced from secondary sources for the period of 1980 to 2016. The results of the study reveals that money supply (MS) has positive and significant relationship with the GDP and are strongly correlated, the interest rate (INT) has a negative relationship with the GDP, so also is the exchange rate (EXR), this implies that increase in interest rate will leads to decrease in GDP, while reduction in interest rate will stimulate investment and would lead to economic growth, also exchange rate (EXR) has a negative relationship with GDP, the higher the exchange rate the lower the GDP as the value of the local currency depreciates.. The paper then recommends amongst others that the monetary authorities should ensure adequate supply of foreign exchange earnings in the economy so as to stabilize and make the local currency to be appreciated.